2018
DOI: 10.1097/anc.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Provider Perceptions of Bubble Continuous Positive Airway Pressure and Barriers to Implementation in a Level III Neonatal Unit in South India

Abstract: Further research will need to focus on whether bCPAP can be safely implemented at level II NICUs.Video Abstract Available at https://journals.lww.com/advancesinneonatalcare/Pages/videogallery.aspx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Important characteristics of various CPAP devices described across the studies included ease of use [ 25 27 , 29 , 34 , 35 ] and effectiveness [ 26 , 28 , 30 , 32 , 34 , 35 ]. Ease of use referred to experiences around simple set ups or low maintenance CPAP devices, while effectiveness related to a device’s overall ability to provide quality care.…”
Section: Resultsmentioning
confidence: 99%
“…Important characteristics of various CPAP devices described across the studies included ease of use [ 25 27 , 29 , 34 , 35 ] and effectiveness [ 26 , 28 , 30 , 32 , 34 , 35 ]. Ease of use referred to experiences around simple set ups or low maintenance CPAP devices, while effectiveness related to a device’s overall ability to provide quality care.…”
Section: Resultsmentioning
confidence: 99%
“…While we did not find any research in LMICs on the use of NIV in transportation settings, previous work on the effectiveness of bCPAP in LMIC hospitals called for further investigation into transportation and highlighted it as a key link to improve respiratory care (31,32); (Dada et al under review). In LMICs, additional factors such as long transport times, limited availability of appropriate training, limited resources in health facilities, and low population density must be considered in the implementation of NIV (23,26).…”
Section: Niv During Transportation In Lmicsmentioning
confidence: 67%
“…Clinical bCPAP programs in low-resource settings have faced challenges. 14 - 16 A country-wide survey in Kenya revealed that only 19 health centers were using bCPAP to treat newborns in 2017. 17 This report indicated that challenges at centers with bCPAP included lack of training of health care providers and poor maintenance of donated equipment.…”
Section: Discussionmentioning
confidence: 99%